2016
DOI: 10.1074/mcp.m116.058925
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KRAS and BRAF Drive Metabolic Reprogramming in Colorectal Cancer

Abstract: Metabolic reprogramming, in which altered utilization of glucose and glutamine supports rapid growth, is a hallmark of most cancers. Mutations in the oncogenes KRAS and BRAF drive metabolic reprogramming through enhanced glucose uptake, but the broader impact of these mutations on pathways of carbon metabolism is unknown. Global shotgun proteomic analysis of isogenic DLD-1 and RKO colon cancer cell lines expressing mutant and wild type KRAS or BRAF, respectively, failed to identify significant differences (at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 66 publications
9
84
0
Order By: Relevance
“…PRM has been successfully used for multiplex quantitation of cytosolic [90] or soluble serum proteins [91]. Towards that goal, we selected xenotropic and polytropic retrovirus receptor 1 (XPR1) as a model surface protein that was found upregulated on the MCF10A-KRas G12V surface via SGM proteomics (Supplementary Table S7B).…”
Section: Resultsmentioning
confidence: 99%
“…PRM has been successfully used for multiplex quantitation of cytosolic [90] or soluble serum proteins [91]. Towards that goal, we selected xenotropic and polytropic retrovirus receptor 1 (XPR1) as a model surface protein that was found upregulated on the MCF10A-KRas G12V surface via SGM proteomics (Supplementary Table S7B).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, targeted MS is ideal for the analysis of clinical specimens, including formalin-fixed, paraffin-embedded (FFPE) sections (34). PRM provides a platform to systematically configure multiplexed, targeted assays for simultaneous analysis of dozens of proteins, thereby enabling focused quantitative analysis of biological systems and pathways (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, targeted MS is ideal for the analysis of clinical specimens, including formalin-fixed, paraffin-embedded (FFPE) sections (34). PRM provides a platform to systematically configure multiplexed, targeted assays for simultaneous analysis of dozens of proteins, thereby enabling focused quantitative analysis of biological systems and pathways (35,36).Here we describe the development of an addressable fractionation-PRM platform, which provides measurements of PD-1, PD-L1 and PD-L2 at femtomole per microgram tissue protein levels in FFPE sections of human melanoma biopsies. We compared our analyses to IHC measurements of PD-L1 in adjacent sections and further characterized the effects of variable cellular composition on measured PD-1, PD-L1 and PD-L2.…”
mentioning
confidence: 99%
“…Although transcriptome profiles are not associated with specific mutations, the frequency of KRAS mutation varies among the CRC subtypes (23% in CMS1, 28% in CMS2, 68% in CMS3, and 38% in CMS4), these data suggest mutations may drive distinct programs of metabolism gene expression [7]. Mutations in KRAS or BRAF genes appear to play an important role in the regulation of metabolic reprogramming in multiple cancers, including CRC [8][9][10][11]. In this study, two established and common prognostic biomarkers in CRC were investigated: KRAS and BRAF mutation status.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, the main goal of our study was to characterize the functional activity of mitochondrial OXPHOS among premalignant polyps and CRC, taking into account their KRAS and BRAF mutation status. To date, it has been shown that KRAS and BRAF mutations increase the glycolytic capacity of tumor cells and their glutaminolysis [8,35]. In our work, the function of the OXPHOS system was analyzed by means of high-resolution respirometry using freshly prepared postoperative tissue samples.…”
Section: Introductionmentioning
confidence: 99%